Impact of Diabetes on Stroke Risk and Outcomes: Two Nationwide Retrospective Cohort Studies. Issue 52 (December 2015) - Liao, Chien-Chang; Shih, Chun-Chuan; Yeh, Chun-Chieh; Chang, Yi-Cheng; Hu, Chaur-Jong; Lin, Jaung-Geng; Chen, Ta-Liang
Abstract : Abstract: Several limitations existed in previous studies which suggested that diabetic patients have increased risk of stroke. We conducted this study to better understand the stroke risk and poststroke outcomes in patients with diabetes. From the claims data of Taiwan's National Health Insurance, we identified 24, 027 adults with new-diagnosed diabetes and 96, 108 adults without diabetes between 2000 and 2003 in a retrospective cohort study. Stroke events (included hemorrhage, ischemia, and other type of stroke) during the follow-up period of 2000 to 2008 were ascertained and adjusted risk of stroke associated with diabetes was calculated. A nested cohort study of 221, 254 hospitalized stroke patients (included hemorrhage, ischemia, and other type of stroke) between 2000 and 2009 was conducted. Adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were calculated for adverse events after stroke hospitalization in patients with and without diabetes. The incidences of stroke in cohorts with and without diabetes were 10.1 and 4.5 per 1000 person-years, respectively. During the follow-up period, diabetic patients had an increased risk of stroke (adjusted hazard ratio: 1.75; 95% CI: 1.64–1.86) than those without diabetes. Associations between diabetes and stroke risk were significant in both sexes and all age groups. Previous diabetes was associated with poststroke mortality (OR: 1.33; 95% CI: 1.19–1.49), pneumonia (OR: 1.30; 95% CI: 1.20–1.42), and urinary tract infection (OR: 1.66; 95% CI: 1.55–1.77). The impact of diabetes on adverse events after stroke was investigated particularly in those with diabetes-related complications. Diabetes was associated with stroke risk, and diabetic patients had more adverse events and subsequent mortality after stroke.